Fire Retardant Treatment of Paper - Shukla, K. S.; Kukreja, P. S.; Tewari, M. C.; Singh, Man Mohan; Guha, S. R. D. (Indian Forester, 1974)
Results of all investigation on treatment of paper by deeping in different fire retardant formulations are reported. Best results were obtained using Borax which imparted fire resistance.